TREATING CHRONIC ANAL FISSURE: A NON-RANDOMIZED CONTROLLED TRIAL COMPARING BOTULINUM TOXIN INJECTION AND LATERAL INTERNAL SPHINCTEROTOMY - Dr. Umair Ahmed; Dr. Muhammad Zulqarnan; Dr. Aisha Arshad; Dr. Muhammad Hassan Azad; Dr. Adil Dawach; Dr. Daniyal Mehboob Panhwar; Dr. Duaa Fatima; Dr. Haadia Safdar; Dr. Muhammad Shehbaz (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The administration of botulinum toxin through an injection within the sphincter muscle has emerged as a possible substitute for the traditional method of treating chronic anal fissure, which involves cutting the internal sphincter muscle on the side. This non-randomized study aimed to investigate the effects of botulinum toxin injection therapy and lateral internal sphincterotomy on reducing anal sphincter pressure in persons with chronic anal fissure. Anal manometry measurements were conducted prior to and two weeks following interventions, and individuals with the condition were had the option to choose between the two treatment techniques. Following the therapy, there was a significant decrease in the maximal resting pressures of both groups, and the magnitude of this impact was similar. The botulinum toxin group successfully decreased sphincter pressures, as evidenced by a substantial decrease in maximal squeeze forces. The healing rates for fissures were comparable between the groups treated with botulinum toxin and those who underwent surgery, with rates of 70% and 82% respectively. Throughout the 14-month observation period, there were no instances of recurring cracks. Botulinum toxin injection and lateral internal sphincterotomy demonstrated comparable efficacy in the treatment of chronic anal fissure, suggesting that both approaches are viable alternatives.